Influence of affecting attributes on tourist behavioural intention to visit Malaysia as a halal tourism destination - Ulfy, Mohammad Arije; Haque, A. K. M. Ahasanul; Karim, Md Wasiul (2020)
Tourism development and investigation acknowledge is the growing interest in Halal tourism. Halal tourism can be described in accordance with Islamic principles with every substances or activity that can use or participate in tourism. Consequently, the significance of Halal Tourist Destination creation and promotion should be cantered in all areas of tourism with the implementation of Islamic guidelines and ethics. Today, demand for halal tourism has increased dramatically and highlighted as one of the new horizons and fastest-growing sector in the world's tourism industry. Malaysia is indeed one of the countries with the most concerned halal segment in the tourism sector. The key purpose of this study is to examine the influence of affecting attributes on tourist’s behavioural intention to visit Malaysia as a halal tourism destination. The development of the research framework is based on the theory of plan behaviour (TPB) model. A total of 395 responses will be collected from the Klang Valley area of Malaysia. For the purpose of processing and analysing the data, SEM-AMOS will be employed. Findings from the study may reveal that, affecting attributes like, "Halal Certification for Food and Beverage", "Destination Image" and "Emotional Incidents" have a significant positive influence on tourist's satisfaction towards behavioural intention to determine the destination. The key outcomes of this research may specify that a good number of Muslim travellers contemplate halal tourism products and services in exploring Muslim approachable destinations, are willing to witnessing Islamic Cultures. The results of this study will provide insight into the behavioural intentions of Muslim tourists to select Malaysia as a tourism destination.